Emerging trends on the topic of information technology in the field of educational sciences: A bibliometric exploration - Carlos Luis GONZÁLEZ-VALIENTE (Ediciones Universidad de Salamanca, 2015)
The paper presents a bibliometric analysis on the topic of Information Technology (IT) in the field of Educational Sciences, aimed at envisioning the research emerging trends. The ERIC data base is used as a consultation source; the results were subjected to productivity by authors, journals, and term co-occurrence analysis indicators for the period 2009-2013. The productivity of Computers & Education, and Turkish Online Journal of Educational Technology-TOJET, as well as the preceding authors from Canada, have been emphasized. The more used terms are the following: Information technology, foreign countries, educational technology, technology integration, and student attitudes. Researches performed here seem to have a largely qualitative character, highlighting computers and internet as the mostly explored technological objects. The largest subject matter trend refers to the integration of IT in the higher education learning context, and its incidence over the teaching methods.